Assessment of wastewater treatment potential of sand beds of River Ganga at Varanasi, India - Singh, Anoop Narain; Mudgal, Ankur; Tripathi, Ravi Prakash; Omar, Padam Jee (Aqua (London, England), 2023)
Inadequate sewage treatment plant (STP) capacity, limited power supply, and discharge of partially treated and raw sewage create a significant sanitation problem in Varanasi city, India. This problem becomes severe during the lean period of the river. To reduce the burden on STPs, sewage can be treated and filtered in a naturally occurring sand bed at the convex bank side of the river. In the present study, a 7-km stretch of the sand bed of River Ganga at Varanasi has been selected. This stretch is divided into three zones: entrance, middle, and exit zones. The objective of this research is to assess the filtration potential of selected sections in respective zones and to find out the most suitable zone, out of the three, for wastewater filtration. Seven basic parameters such as dissolved oxygen, biological oxygen demand, electrical conductivity, total dissolved solids, salinity, pH, and temperature were measured before and after filtration, through the sand bed of the three zones of River Ganga. Of the three selected zones of the river bend, filtration length and the amount of available sand were found to be maximum in the middle zone. Experimental results and survey work show that the sand bed in the middle zone of the river bend is best suited for wastewater disposal and filtration.